1997
DOI: 10.1148/radiology.203.3.9169715
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis of the diabetic foot: MR imaging-pathologic correlation.

Abstract: Marrow edema cannot be reliably distinguished from osteomyelitis with MR imaging. Gadopentetate dimeglumine is of limited use. Some previously published false-positive reports of osteomyelitis were most likely due to edema of the marrow. MR imaging is useful in planning surgery of the infected diabetic foot, as it enables reliable distinction between normal and abnormal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
2
13

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(96 citation statements)
references
References 0 publications
6
75
2
13
Order By: Relevance
“…A study on bone histomorphology showed several pathological findings but did not describe in detail the type of inflammation seen in the 29 cases of osteomyelitis [25]. Other authors studied the correlation between bone histopathology and magnetic resonance imaging in 13 patients [26]. They described three types of osteomyelitis (21 cases) in their 57 bone specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A study on bone histomorphology showed several pathological findings but did not describe in detail the type of inflammation seen in the 29 cases of osteomyelitis [25]. Other authors studied the correlation between bone histopathology and magnetic resonance imaging in 13 patients [26]. They described three types of osteomyelitis (21 cases) in their 57 bone specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomyelitis was diagnosed when focally increased bone marrow signal on FST 2 WI ( fi g. 1 a) and focally decreased marrow signal on T 1 WI with or without cortical destruction, and focal marrow enhancement on postcontrast T 1 WI was observed ( fi g. 1 , 2 ). Normal marrow signal on T 1 WI with high signal on FST 2 WI and marrow enhancement post contrast were also considered as osteomyelitis as reported by other investigators [9,10] . Abscess was diagnosed when a well-defi ned high signal intensity collection was seen in the soft tissues on FST 2 WI with or without thick rim enhancement on post-contrast T 1 W sequences [11] .…”
Section: Mri Criteriamentioning
confidence: 99%
“…Some studies recommend its routine use, (15,20) while others suggest it is unnecessary. (7,21,22) There is no conclusive evidence that intravenous contrast administration increases the accuracy of detection of osteomyelitis, although it certainly improves the evaluation of soft tissue pathology (e.g. abscesses, sinus tracts) and allows distinction between viable and nonviable soft tissue or bone.…”
Section: Mr Imaging Protocolmentioning
confidence: 99%